PENGARUH MARGIN MURABAHAH, BUNGA KPR BANK KONVENSIONAL DAN UJRAH TERHADAP TINGKAT PERTUMBUHAN PEMBIAYAAN KONGSI KEPEMILIKAN RUMAH SYARIAH (KPRS) DI BANK MUAMALAT CABANG MEDAN - Dina Zulfa Opera (Journal Analytica Islamica, 2016)
This research was purposed to find out the effect ofmurabahah margin, financing of mortgage interest of conventional bank, and ujrah toward level of financing of sharia mortgage interest in Medan branch of bank muamalat. The research usedquantitative approach,withmultiple linear regression techniques supportedby classic assumption testand statistic test, assisted by Eviews version 6.0.Based onresults conducted at alpha 5%, the researchherconcluded that, simultaneouslymurabahah margin, financing of mortgage interest of conventional bank, and ujrah toward level of financing of sharia mortgage interest in Medan branch of bank muamalat, which is the value ofF-calculate14,18644bigger thanF-table13,6. Whilepartiallymurabahah margin responded highlythelevel of financing of sharia mortgage interest in Medan branch of bank muamalat, amounted to 38,84%, while ujrah responded positively andsignificant, amounted to 20,52%, and financing of mortgage interest of conventional bankresponded negatively and significant, amounted to -20,81%.